AN ANALYSIS ON THE FOURTH SEMESTER STUDENTS’ ABILITY IN USING PRONOUN AT THE ENGLISH EDUCATION DEPARTMENT OF STKIP INSAN MADANI AIRMOLEK - Gusparia Gusparia; Loly Novita; Fajar Wirawan (Politeknik Negeri Bengkalis, 2022)
The method used to conduct this research was the descriptive qualitative method. The sample of the research was the fourth-semester students of the English Education Department which consisted of 24 students. The aim of this research is to know their ability in using pronouns. To collect the data, a written form of the test was used and it was divided into two categories (multiple choice and essay). The students were then asked to do the test of pronouns of a subject, object, adjective possessive, possessive and reflexive. The design of the test was based on the relevant literature review and the authors’ observation when the teaching and learning process about pronouns took place. After the analysis of the data, the average score obtained from the student's test was 6.4 which belonged to the fair good category. The result of the test showed 23 students (96%) whose abilities were in the middle category, 1 student (4%) whose ability was in the low category, and 0 students (0%) whose ability was in the high category. Even though the results make the authors surprised, the findings of the research can give some points of view for a lecturer to prepare the lesson materials better, apply various teaching techniques to get the student's attention and interest during the teaching-learning process and use various teaching aids to support the success of his teaching so that the students could have better understanding and competence in English.Keywords: Ability, Pronoun